“The United States Cannot Afford to Lag Behind Russia”: Making the Case for an American Nuclear Icebreaker, 1957-1961 - Kikkert, Peter (The Northern Mariner / Le marin du nord, 2021)
Between 1957 and 1961, members of Congress spearheaded efforts to gain authorization for the U.S. Coast Guard to construct a nuclear-powered icebreaker. This article uses congressional hearings, debates, and media coverage to conduct a frame analysis and map the arguments, themes, and stories used to convince decision-makers to build the vessel. While state competition became the central frame used by American nuclear icebreaker proponents, national security, science and technology, an uncertain future, and technical details about the existing fleet’s decline were also popular narratives. Although the push for a nuclear icebreaker enjoyed popular bi-partisan and bi-cameral support in Congress, it failed to convince a budget-conscious Eisenhower administration. De 1957 à 1961, les membres du Congrès se sont efforcés d’obtenir l’autorisation de la Garde côtière américaine de construire un brise-glace à propulsion nucléaire. À l’aide d’audiences du Congrès, de débats et de reportages dans les médias, cet article effectue une analyse de cadre et recense les arguments, les thèmes et les récits qui ont servi à convaincre les décideurs de construire le navire. Alors que les partisans américains des brise-glaces nucléaires se sont principalement fiés à la concurrence entre états comme leur cadre principal, la sécurité nationale, la science et la technologie, un avenir incertain et des détails techniques concernant le déclin de la flotte existante étaient également des conceptions populaires. Bien que la pression en faveur d’un brise-glace nucléaire ait bénéficié d’un appui populaire bipartite et bicaméral au Congrès, elle n’a pas réussi à convaincre l’administration Eisenhower soucieuse de son budget.